2018
DOI: 10.1002/sctm.18-0045
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Mesenchymal Stromal Cell Antioxidant Responses in Progressive Multiple Sclerosis

Abstract: The potential of autologous cell‐based therapies including those using multipotent mesenchymal stromal cells (MSCs) is being investigated for multiple sclerosis (MS) and other neurological conditions. However, the phenotype of MSC in neurological diseases has not been fully characterized. We have previously shown that MSC isolated from patients with progressive MS (MS‐MSC) have reduced expansion potential, premature senescence, and reduced neuroprotective potential in vitro. In view of the role of antioxidants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…The present detection of comparable in vitro phenotypic and immunosuppressive functions of MS MSC and HD MSC are in line with a few previous studies, while others reported on reduced immunosuppressive and neuroprotective function of MS MSC compared to HD MSC [40,41,55,56]. In light of the pronounced clinical effect of allogenic MSC therapy in EAE models, contrasting the modest effect of autologous MSC therapy shown in MS, it has been questioned whether MS MSC have reduced therapeutic capacities compared to HD MSC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present detection of comparable in vitro phenotypic and immunosuppressive functions of MS MSC and HD MSC are in line with a few previous studies, while others reported on reduced immunosuppressive and neuroprotective function of MS MSC compared to HD MSC [40,41,55,56]. In light of the pronounced clinical effect of allogenic MSC therapy in EAE models, contrasting the modest effect of autologous MSC therapy shown in MS, it has been questioned whether MS MSC have reduced therapeutic capacities compared to HD MSC.…”
Section: Discussionsupporting
confidence: 90%
“…The clinical experience of BM MSC therapy in MS is mainly based on studies using autologous cells. However, a few reports have recently demonstrated inferior in vitro immunosuppressive and neuroprotective properties of BM MSCs derived from MS compared to healthy donors (HD) [40,41]. Such findings may be attributed to chronic inflammation and a possible dysfunctional regulation of the BM niche, which raises the concern whether autologous cells may have disadvantages compared to their allogeneic counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS), including oxygen ions, oxygen-free radicals, and peroxides, are byproducts of normal aerobic metabolism. ROS are involved in the regulation of multiple signalling pathways including cell proliferation, survival, and inflammation [212][213][214]. An imbalance between levels of ROS and antioxidant function leads to ROS-related diseases such as ageing, carcinogenesis, immune disorders, inflammation, multiple sclerosis, and neurodegeneration [129,215].…”
Section: Antioxidative Factorsmentioning
confidence: 99%
“…However, studies have shown that a person's age and overall health can affect their MSC in ways that may impact a proposed therapy [12]. A report in STEM CELLS TRANSLATIONAL MEDICINE showed that MSC isolated from ©AlphaMed Press 2018 STEM CELLS patients with progressive multiple sclerosis (MS), a disease characterized by inflammatory demyelination in the central nervous system, exhibit a marked reduction in the anti-inflammatory properties that are hallmarks of MSC-based therapies, leading to reduced neuroprotective potential [13]. Redondo et al explored these cells' susceptibility to oxidative and nitrosative stress and found that MSC from MS patients (MS-MSC) displayed reduced expression of important antioxidants superoxide dismutase 1 and glutathione S-transferase P and their master regulators, nuclear factor erythroid 2-related factor 2 and peroxisome proliferator-activated receptor gamma coactivator 1-α.…”
Section: Mesenchymal Stem Cell Dysregulation In Patients With Multiplmentioning
confidence: 99%